Understanding Consumer Buying Intention of E-Commerce Airfares Based on Multivariate Demographic Segmentation: A Multigroup Structural Equation Modeling Approach - Naruetharadhol P. (2023)
The internet offers enormous development opportunities for airline firms and a lot of information for consumers to pick the finest available options. This research aims to study the consumer buying intention of e-commerce airfares in an emerging economy based on the technology acceptance model. This article employed a sample of 3064 respondents at six airports in Thailand. It used cluster analysis (a multivariate analysis approach) to determine two main customer segments and then used a structural equation modeling (SEM) technique utilizing demographic segmentation as a moderator to explain the behaviors of those two segments. The findings demonstrated two customer segments: (1) the older with high and middle-income segment, and (2) the young with low-income segment. The empirical results revealed that price sensitivity and perceived ease of use substantially impacted behavioral intention to use e-commerce airfares in both segments. The users from segment (1) are more likely to look for the fun experience and entertainment value of using e-commerce airfares than those from segment (2). However, perceived usefulness is unlikely to be a vital factor in consumers’ purchasing decisions about using e-commerce airfares. It is recommended that airline companies and online travel agencies should consider perceived ease of use, price sensitivity, and hedonic motivation when implementing e-commerce airline websites for selling tickets.